Validity and Reliability of a Research Instrument on the Learning Outcome of Automotive Engineering - Ranu Iskandar; Putri Khoirin Nashiroh (International Journal of Educational Practice and Policy, 2026)
Before use, research instruments must be proven valid and have an estimate of their reliability, so instruments can measure what they are intended to measure and be used at different times. The objectives of this study are (1) to prove the validity of the questionnaire instrument for the Learning Outcomes of SMK Automotive Engineering Students and (2) to estimate the reliability of the questionnaire instrument for the Learning Outcomes of SMK Automotive. The study employed a descriptive quantitative design. The instrument was reviewed by eight expert judges and piloted with 30 vocational high school students. Validity was assessed using the Content Validity Index (CVI), Content Validity Ratio (CVR), average variance extracted/discriminant evidence, and outer loading, while reliability was examined through percent agreement and Cronbach’s alpha. The findings showed very strong content validity, with I-CVI values ranging from 0.875 to 1.000, CVR values from 0.80 to 1.00, S-CVI/ave of 0.988, and AVE > 0.50. All outer loadings ranged from 0.795 to 0.914. All constructs met the Fornell–Larcker criterion, percent agreement reached 100%, and Cronbach’s alpha ranged from 0.868 to 0.892. These results indicate that the instrument is valid, reliable, and appropriate for further research on determinants of automotive learning outcomes.